Economic evaluation of an integrated care programme for patients with hand dermatitis. (28th June 2013) - van Gils, Robin F.; Bosmans, Judith E.; Boot, Cécile R. L.; Rustemeyer, Thomas; van Mechelen, Willem; van der Valk, Pieter G. M.; Anema, Johannes R.
Summary Background Hand dermatitis has a large impact on society as a whole. Objectives To evaluate the cost‐effectiveness of integrated, multidisciplinary care as compared with usual care (UC) for patients with moderate to severe chronic hand dermatitis after 52 weeks. Methods Patients (n = 196) visiting the dermatology department at one of the participating hospitals for hand dermatitis were randomized to integrated care (IC) or UC. IC was provided by a multidisciplinary team, and integrated clinical and occupational care to optimize treatment of hand dermatitis. Effect outcomes were clinical assessment of hand dermatitis with the Hand Eczema Severity Index (HECSI), and disease‐specific quality of life, work performance and quality‐adjusted life‐years with the EQ‐5D. Incremental cost‐effectiveness ratios (ICERs) were calculated. The ICER indicates the additional investment needed to gain one unit of effect. Results The HECSI difference between both groups after 52 weeks was 8.7 (standard error 5.3, 95% confidence interval −1.8–18.9). No differences were found on secondary outcome measures. Mean total costs with IC (€3613; SD 798) were significantly higher than with UC (€1576, SD 430). The ICER for improvement in HECSI score was − 247. IC was not considered to be cost‐effective as compared with UC. The probability that IC was cost‐effective was 90% at a ceiling ratio of €1500 per additional point improvement in HECSI score. Conclusion Integrated care was neither cost‐effective, nor effective after 12 months follow‐up, in contrast to our findings after 6 months. Decision makers should decide whether the clinical benefits of integrated care on the short term outweigh the higher costs compared to usual care.